2005
DOI: 10.1096/fj.04-3287fje
|View full text |Cite
|
Sign up to set email alerts
|

Somatic DNA damage in interventional cardiologists: a case‐control study

Abstract: Interventional cardiologists who work in cardiac catheterization laboratories are exposed to low doses of ionizing radiation that could pose a health hazard. DNA damage is considered to be the main initiating event by which radiation damage to cells results in development of cancer and hereditary disease. The aim of the present study was to assess the effects of chronic low-dose X-ray radiation exposure on somatic DNA damage of interventional cardiologists working in high-volume cardiac catheterization laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 40 publications
6
57
0
2
Order By: Relevance
“…The interventional group working in a high-volume catheterization laboratory had higher levels of MN, when compared with diagnostic. Years of radiological practice were correlated with the MN value in the exposed group, which suggests the presence of cumulative damage (Andreassi et al, 2005). Furthermore in this study the MN frequency in the exposed the groups based on the duration work length of employment as shown in Figure 6.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…The interventional group working in a high-volume catheterization laboratory had higher levels of MN, when compared with diagnostic. Years of radiological practice were correlated with the MN value in the exposed group, which suggests the presence of cumulative damage (Andreassi et al, 2005). Furthermore in this study the MN frequency in the exposed the groups based on the duration work length of employment as shown in Figure 6.…”
supporting
confidence: 54%
“…6, (Andreassi et al, 2005) reported the similar result that was no significant correlation between occupational radiation doses during the past year and MN frequency. (Zakeri & Hirobe, 2010) also reported that no obvious trend of increased chromosomal damages as a function of either duration of employment, exposed dose, sex or age.…”
mentioning
confidence: 69%
“…Promieniowanie jonizujące, jakim jest promieniowanie rtg., wywiera niekorzystny wpływ na poziomie komórkowym, ze wzrostem wielkości emitowanej dawki, wywołując zmiany ogólnoustrojowe oraz inicjacje zmian miejscowych [4,5,19].…”
Section: Omówienieunclassified
“…For instance, the average dose of 15 mSv confers a risk of one extra-cancer in every 750 exposed 50-yearold male paients, but the risk is 38% higher in women, must be muliplied by 4 in children, and is reduced by 50% in an 80-year-old man. The risk is higher in presence of some unfavorable polymorphisms of genes involved in DNA repair and in presence of other environmental carcinogens such as smoking 20,21 . The risk can probably be reduced with chemoprotecive strategies, for instance with ani-oxidant cocktails 22 , although the cost-beneit assessment of these strategies remains unsetled.…”
Section: The Order Of Magnitude and Risksmentioning
confidence: 99%